Poems of William Blake - Blake, William (Saga Egmont, 2020)
The following work is a collection of poems written by William Blake. He was an English poet, painter, and printmaker. Largely unrecognized during his life, Blake is now considered a seminal figure in the history of the poetry and visual art of the Romantic Age. What he called his "prophetic works" were said by 20th-century critic Northrop Frye to form "what is in proportion to its merits the least read body of poetry in the English language". Titles to be found in this book include 'The Echoing Green', 'The Lamb', and 'The Blossom.'